REGIONAL FEATURES OF TRANSFORMATION OF SCIENTIFIC AND EDUCATIONAL POTENTIAL IN UKRAINE - Slokva, Maryna (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The article is devoted to the analysis of the scientific and educational potential of the regions of Ukraine, the determination of the scope and directions of its transformation against the background of comparison with the economic indicators of different territories. In the recent years, in conditions of military conflict in eastern Ukraine all sectors of the economy, including education sector, have undergone significant changes. Moving of higher education institutions, students, teaching staff to the territory, controlled by Ukraine, has led to the transformation of scientific and educational potential not only of Donetsk and Lugansk regions and the Autonomous Republic of Crimea, but also of other regions of the country. The main goal of higher education industry is to meet the needs of the economy in the specialists of relevant profile and level of qualification, directly in the region, where the higher education institution is located. It determines the importance of the scientific and educational potential of the region as a determinant of the provision of the regional economy of skilled workforce. Prior to the outbreak of the military conflict, Donbas, as a powerful region of the country, not only in economic, but also in scientific and educational sphere, was characterized by significant indicators of activity. For example, in 2013, Donetsk region ranked sixth among the regions of Ukraine in terms of the number of higher education institutions, the number of students, the number of students admitted to the first year of study and the number of teaching staff; in terms of graduates from higher education institutions, the number of teachers with scientific degrees and academic titles it was the fifth; in terms of gross regional product it was the second after Kyiv; and it was the first in terms of population engaged in economic activity. At present, the positions of Donetsk region have shifted. In terms of a number of higher education institutions, this region, together with Khmelnitsky and Kherson regions, is ranked seventh; by the number of teaching staff – it’s fourteenth; by the number of the students admitted to the first course, teachers with academic degrees it is on the fifteenth place; by the number of teachers with scientific titles – on the sixteenth one, in terms of the specialists graduates from higher education institutions – on the nineteenth one. At the same time Donetsk region is the seventh largest in terms of economic activity and the fourth largest in terms of gross regional product. On the other hand, during the last years such regions, as Vinnitsa, Dnipropetrovsk, Kharkiv ones and Kyiv city, where higher educational establishments were moved from non-controlled territories, show growth of scientific and educational potential. Obvious transformations of the regions scientific and educational potential lead to disproportions in the development of the higher education services market.